Congenital Absence of Gall Bladder (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Congenital absence of gall bladder is a very rare entity found in clinical practices. Due to miss interpretation of  sonographic findings as they are not familiar with the condition it possess a great difficulty in management the  patient. Though the patient present with the feature of acute  cholecystitis, conservative treatment is enough to cure the disease. Modern radiological intervention make the diagnosis confirm, thus preventing unnecessary surgical procedure. Here we report two cases of Congenital absence of gall bladder presenting as acute cholecystitis ultimately  diagnosed and treated. DOI: http://dx.doi.org/10.3329/jbcps.v30i3.12470 J Bangladesh Coll Phys Surg 2012; 30: 177-180